LDx: An electronic storyboard that supports the users' requirements process in developing a user interface for the clinician-researchers team. - Arce Olivares Hanlon, Rolando Israel (Trinity College Dublin. School of Computer Science & Statistics. Discipline of Computer Science, 2023)
This thesis presents the development of an electronic storyboard named LDx, which stands for Linked Data Experience, to facilitate the users' requirements gathering in developing a future user interface to support data exploration, data quality and data integration tasks in the healthcare domain. In the healthcare domain members of a clinician-researchers team find it difficult to directly interact with data repositories and Linked Data datasets to undertake common tasks that they typically need to do to explore their research hypotheses. I proposed the development of a tool, an electronic storyboard, that integrates the common tasks involved through one user interface to support data exploration, data quality assessment and data integration tasks. To initiate the necessary user-centred design process, I designed the LDx electronic storyboard to facilitate the user requirements gathering process. The LDx electronic storyboard consists of a graphical user interface that includes data exploration, data quality and data integration sections. The LDx electronic storyboard was evaluated in terms of its efficiency and user satisfaction via one usability test - a Think-Aloud Test. The participants of the first experimental study were members of a clinician-researchers team (including principal investigators and research managers). A second experimental study was conducted to support and verify users' requirements for developing a future user interface via a triangulation technique (including interviews and direct observations). The participants of the second experimental study were members of a clinician-researchers team (including principal investigators, researchers and statisticians). This research has yielded one major contribution, the design, development and evaluation of the LDx electronic storyboard, to support the users? requirement gathering, and two minor contributions. The first minor contribution is the state-of-the-art review of user interfaces/tools in the healthcare domain to identify problems that the electronic storyboard intends to address. The second minor contribution is the inclusion of direct observations in the Triangulation approach to support and verify the users? requirements process. The contributions described in this thesis could be transferred to any other domain in order to enhance user engagement and ease data exploration, quality, and integration tasks.
APPROVED
Keywords: electronic storyboard, data integration, semantic web, thematic analysis, triangulation